Dilemma: Quality or quantity in scientific periodical publishing - Melnyk, Yu. B.; Мельник, Ю. Б.; Pypenko, I. S. (International Journal of Science Annals. - 2021. - Vol. 4, № 2. - Р. 5-7, 2021)
Journals should be committed to a high standard of editorial ethics. Journals should have a clear and precise procedure for reviewing and selecting papers for publication. Journals should necessarily consider the possible conflict of interest in research between authors, editors, reviewers, funders, etc. Journals should motivate young talented scientists to publish their manuscripts by providing them with editorial support in the preparation of the manuscript and funding for its publication. The implementation of these key principles will contribute both to the development of science in general and the Journal in particular. Scientific periodicals should solve the dilemma of quality and quantity of papers definitely in favor of quality. Journals should be committed to a high standard of editorial ethics. Journals should have a clear and precise procedure for reviewing and selecting papers for publication. Journals should necessarily consider the possible conflict of interest in research between authors, editors, reviewers, funders, etc. Journals should motivate young talented scientists to publish their manuscripts by providing them with editorial support in the preparation of the manuscript and funding for its publication. The implementation of these key principles will contribute both to the development of science in general and the Journal in particular.

Наукові періодичні видання повинні вирішувати дилему якості та кількості статей однозначно на користь якості. Журнали повинні дотримуватися високих стандартів редакційної етики. Журнали повинні мати чітку та точну процедуру рецензування та відбору статей для публікації. Журнали повинні обов'язково враховувати можливий конфлікт інтересів у дослідженнях між авторами, редакторами, рецензентами, спонсорами тощо. Журнали повинні мотивувати молодих талановитих науковців публікувати свої рукописи, надаючи їм редакційну підтримку у підготовці рукопису та фінансуванні його публікації. Впровадження цих ключових принципів сприятиме розвитку як науки загалом, так і журналу зокрема.
Keywords: journals; scientific periodical; scientific periodicals; quality; quantity; наукові періодичні видання; якість; кількість